A New Perspective on Jesus : What the Quest for the Historical Jesus Missed - Dunn, James D. G., 1939-2020. (Grand Rapids, Mich. : Baker Academic, 2005)
In A New Perspective on Jesus, renowned author James D. G. Dunn critiques the quest for the historical Jesus. He claims that the quest has been largely unsuccessful because it started from the wrong place, began with the wrong assumptions, and viewed the evidence from the wrong perspective. Dunn's study offers three criticisms of questers' methods. First, Dunn contends that scholars have failed to see how the disciples' pre-Easter faith shaped the Gospel traditions. Second, he claims that a focus on literary transmission has led scholars to ignore the fact that the Gospel traditions arose in an oral culture, which shaped the way the stories of Jesus were told and passed on. Third, Dunn challenges scholars' preoccupation with finding what is distinctive about Jesus and rejecting portions of the tradition portraying Jesus as characteristically Jewish. Dunn concludes by rethinking accepted views of Synoptic relationships in light of the oral nature of the Jesus tradition. This work offers a compelling critique of the presuppositions that inform much of contemporary Gospel study, and the alternatives Dunn proposes are sure to stimulate scholarly debate. It will interest students and scholars of the Bible, pastors and church leaders, and anyone wanting a fresh perspective on Jesus studies--from publisher's website.
First Faith : When Did Faith Become a Factor in the Jesus Tradition? -- Behind the Gospels : What It Meant to Remember Jesus in the Earliest Days -- Characteristic Jesus : From Atomistic Exegesis to Consistent Emphases -- Appendix: Altering the Default Setting : Re-envisaging the Early Transmission of the Jesus Tradition.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Historicity -- History of doctrines -- 20th century; Jesus Christ -- History of doctrines -- 20th century; Historical Jesus - New Perspective; Christology - Traditional Concerns; Evidences of Jesus Christ